The double‐periodic analog of the Cauchy kernel and some its applications - Dzehtsiarenka, N. A.; Zverovich, E. I. (Mathematical Modelling and Analysis, 1998)
A new analytic expression for the double‐periodic analog of the Cauchy kernel is proposed and its explicit form is presented. Some applications of this analog are given.First Published Online: 14 Oct 2010